Assessment of knowledge, attitudes, and practices towards Zika virus among healthcare workers in St. Kitts - Francis, Donya L. (BMC Infect Dis, 2021)
BACKGROUND: Healthcare workers are usually the first responders during outbreaks and are instrumental in educating the populace about the prevention of different diseases and illnesses. The aim of this study was to assess the association between healthcare workers’ characteristics and knowledge, attitudes and practices toward Zika virus. METHODS: This was a cross-sectional study that collected data from healthcare workers at 3 medical facilities using a validated self-administered questionnaire between July 2017 – September 2017. Logistic regression models were used to examine the association between sociodemographic and knowledge, attitudes, and practices. RESULTS: A total of 190 healthcare workers were analyzed. Of these, 60, 72.6 and 64.7% had good knowledge, positive attitudes, and good practices toward Zika virus, respectively. Healthcare workers without a formal degree were less likely to have good knowledge of Zika virus (adjusted odds ratio (AOR) = 0:49; 95% confidence interval (CI) = 0.24–0.99) compared to those with a formal degree. Reduced odds for positive attitude towards Zika virus were observed in healthcare workers with low income as compared to those with high income (AOR = 0.31; 95% CI =0.13–0.75). Being younger than 40 years old was associated with poor Zika virus practices (AOR = 0:34; 95% CI = 0.15–0.79). CONCLUSIONS: Significant association between healthcare workers’ sociodemographic characteristics and Zika virus knowledge, attitudes and practices were observed. Public health interventions that seek to increase Zika virus awareness should aim to train healthcare workers who are younger, without formal degree and those earning low income.